2021
DOI: 10.1177/08982643211042159
|View full text |Cite
|
Sign up to set email alerts
|

Couple Religiosity and Well-Being Among Older Adults in the United States

Abstract: Objectives: This article evaluates whether couples’ religious similarity is consequential for the health of older married men and women. Alternatively, we examine whether women’s religiosity alone is health-protective to their husbands . Methods: Using dyadic data from the US National Social Life, Health, and Aging Project, a representative sample of 913 individuals ages 62–91 plus their marital partners, we perform latent-class analysis to separate older couples into classes based on religious characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…It would also be instructive to look at how religious/spiritual struggles, defined as conflicts or tensions about spiritual beliefs, the divine, or other religious members (Stauner et al 2016), may factor into how workers deal with work-family strain. Finally, given that work-family conflict is a stressor which occurs at the familial level, we would also recommend that future studies move beyond individual-level measures of religiosity and begin to examine dyadic measures of religion/spirituality at the partner level (Upenieks, Uecker, and Schafer 2022) or between parents and children (Flor and Knapp 2001). Doing so will allow for a greater understanding of how any stress-buffering or stress-exacerbating effects of religiosity may be contingent on the joint (concordant/discordant) religious beliefs in these dyads.…”
Section: Discussionmentioning
confidence: 99%
“…It would also be instructive to look at how religious/spiritual struggles, defined as conflicts or tensions about spiritual beliefs, the divine, or other religious members (Stauner et al 2016), may factor into how workers deal with work-family strain. Finally, given that work-family conflict is a stressor which occurs at the familial level, we would also recommend that future studies move beyond individual-level measures of religiosity and begin to examine dyadic measures of religion/spirituality at the partner level (Upenieks, Uecker, and Schafer 2022) or between parents and children (Flor and Knapp 2001). Doing so will allow for a greater understanding of how any stress-buffering or stress-exacerbating effects of religiosity may be contingent on the joint (concordant/discordant) religious beliefs in these dyads.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings echo this body of literature and indicate couple interdependence in physical activity as a common phenomenon across various countries/cultures, including China. While three potential mechanisms (i.e., assertive mating, social control, and shared resources) are suggested in existing literature (Lu & Shelley, 2019;Smith & Zick, 1994;Umberson, 1992), further investigations are needed to examine or compare these hypotheses in explaining spousal concordance in physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…First, the assortative mating mechanism proposes that individuals are more likely to marry those with comparable sociodemographic and behavioral characteristics, such as health behaviors (Lillard & Panis, 1996). Second, according to the social control hypothesis, one may exert social control over one's partner's health behaviors, such as regulating the other's risky health behaviors and promoting healthy behaviors, to promote health for both partners (Lewis & Rook, 1999;Umberson, 1992). Third, the shared resources or linked lives hypothesis posits that couples share same household and community environments and social networks that promote and/or hinder health behaviors of both partners (Smith & Zick, 1994).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, empirical studies have consistently shown that a shared religious background in marital relationships tends to positively influence the quality of the marital relationship (Hwang et al, 2019; Schafer & Kwon, 2019). Couples with similar religious backgrounds tend to have higher levels of marital satisfaction as they procure psychological and social stability through similar religious beliefs (Ellison et al, 2010; Upenieks et al, 2022), and they also have higher levels of social interactions with friends or neighbors by expanding the social network of individuals and spouses through religious institutions (Stadtfeld & Pentland, 2015). Considering the ‘ sacramental marriage ’ in the Catholic doctrine as an example that most religions encourage marriage within the same religion, a higher level of social interactions or support can be obtained within the social relationships formed around religious groups, as couples with similar religious backgrounds can be considered ‘good followers’ of these religious doctrines (Sorenson et al, 1995).…”
Section: Introductionmentioning
confidence: 99%